2017
DOI: 10.1007/s10900-017-0453-1
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Travel Characteristics of Travel-Associated Zika Virus Infection Case-Patients in San Diego County, California (January 1, 2016–March 31, 2017)

Abstract: Most Zika disease cases diagnosed in the continental US have been associated with travel to areas with risk of Zika transmission, mainly the Caribbean and Latin America. Limited information has been published about the demographic and travel characteristics of Zika case-patients in the United States, besides their age and gender. During 2016–2017 the County of San Diego Health and Human Services Agency, California, expanded the scope and completeness of demographic and travel information collected from Zika ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Among ZIKV-infected travelers, however, the gender ratio was 1.0-suggesting that referral bias rather than gender-based disease load may account for the increase in female over male patients seen in endemic countries. Thus, our data confirm reports from other series in travelers 17 and is contrary to studies from endemic countries that reported gender inequality. 18,19 Zika virus infection is mostly perceived to be a mild infection.…”
Section: Discussionsupporting
confidence: 90%
“…Among ZIKV-infected travelers, however, the gender ratio was 1.0-suggesting that referral bias rather than gender-based disease load may account for the increase in female over male patients seen in endemic countries. Thus, our data confirm reports from other series in travelers 17 and is contrary to studies from endemic countries that reported gender inequality. 18,19 Zika virus infection is mostly perceived to be a mild infection.…”
Section: Discussionsupporting
confidence: 90%
“…Human mobility has long been associated with the introduction of infectious disease pathogens, transmission, and propagation globally. Severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and Zika virus are contemporary examples of outbreaks that underscore the role of mobility, travel, and migration in the spread of infectious diseases [ 1 3 ]. Conflict, insecurity, fear of persecution, natural disasters, and environmental pressures have contributed to population displacement.…”
Section: Introductionmentioning
confidence: 99%